Wpływ mediów elektronicznych na sen nastolatków żydowskich i arabskich - Salah abo Ganim, Sondos Ali (Studia Edukacyjne, 2020)
Sleep is important to physical and mental development. Studies show that adolescents suffer from electronic media exposure-related inadequate and non-quality sleep. In Israel, traditional, conserva-tive Arab society is undergoing a modernization process with exposure to the Western lifestyle and Israeli Jewish culture. This comparative cross-sectional study compared electronic media exposure’s impact on sleep in secular Jewish and Arab society in Israel, involving 229 middle and high school adolescents, 118 Arabs and 111 Jews. Research tools were the School Sleep Habits Survey (SSHS) and a sociodemographic questionnaire. Jewish adolescents are more exposed to electronic media than are Arab adolescents only during mid-week. Weak but significantcorrelations were found between late night use of electronic media and sleep duration; increased exposure to television (r = -0.17, p = .01), mobile telephone r = -0.21, p = .002), and tablet (r = -0.14, p = .02) related to shorter sleep duration and longer sleep latency mid-week in both groups and later weekend wake-up time. Arab adolescents are sleepier during the day and have more sleep-related behavior problems. As electronic media exposure rises, sleep duration shortens, and sleep time is postponed in both cultures. Exposure to electronic media is higher among Jewish adolescents. Boys sleep longer than girls during the week (a difference of nearly an hour).